Longitudinal Measurement Invariance of the Authoritative School Climate Survey. (September 2021) - Konold, Tim R.; Edwards, Kelly D.; Cornell, Dewey G.
This study evaluated the longitudinal psychometric properties of the Authoritative School Climate Survey (ASCS) using a statewide sample of middle and high schools across 8 years. Multilevel confirmatory factor analyses were conducted to test the longitudinal measurement invariance of three scales on the ASCS: disciplinary structure, teacher respect for students, and students' willingness to seek help. These scales demonstrated strong factorial invariance across all time points for both middle and high schools. Results support the use of these scales in evaluating longitudinal change in school climate.